Technologies of reproduction across the lifecourse : expanding reproductive studies - Boydell, Victoria; Dow, Katharine (Emerald studies in reproduction, culture and society., 2022)
>Human reproduction is mediated through many technologies, both high- and low-tech. These technologies of reproduction are not experienced in isolation by most of the people who use them. However clinical, public health and social scientific research often reflects a parcelling out of reproduction into specialist areas of biomedical intervention. Studies tend to be bound to specific physiological events, technologies (particularly those that are more obviously technical or 'modern') and people - namely cis, heterosexual, white, middle-class women. Yet, with the ever-expanding horizon of reproductive technologies and the rapid development of the fertility industry, the reality is that many individuals will engage with more than one such technology at some point in their life. >Technologies of Reproduction Across the Lifecourse presents dialogue between scholars on different reproductive technologies not only from a comparative empirical perspective, arguing that operating in disciplinary silos and working from narrow ideas about RTs and their meanings can put reproductive studies in danger of missing, and thereby reproducing, the kinds of power structures that shape reproductive life.